The Drosophila melanogaster homolog of UBE3A is not imprinted in neurons. Issue 9 (1st September 2016) - Hope, Kevin A.; LeDoux, Mark S.; Reiter, Lawrence T.
ABSTRACT: In mammals, expression of UBE3A is epigenetically regulated in neurons and expression is restricted to the maternal copy of UBE3A . A recent report claimed that Drosophila melanogaster UBE3A homolog ( Dube3a ) is preferentially expressed from the maternal allele in fly brain, inferring an imprinting mechanism. However, complex epigenetic regulatory features of the mammalian imprinting center are not present in Drosophila, and allele specific expression of Dube3a has not been documented. We used behavioral and electrophysiological analysis of the Dube3a loss-of-function allele ( Dube3a 15b ) to investigate Dube3a imprinting in fly neurons. We found that motor impairment (climbing ability) and a newly-characterized defect in synaptic transmission are independent of parental inheritance of the Dube3a 15b allele. Furthermore, expression analysis of coding single nucleotide polymorphisms (SNPs) in Dube3a did not reveal allele specific expression differences among reciprocal crosses. These data indicate that Dube3a is neither imprinted nor preferentially expressed from the maternal allele in fly neurons.